Dual-target MDM2/MDMX inhibitor increases the sensitization of doxorubicin and inhibits migration and invasion abilities of triple-negative breast cancer cells through activation of TAB1/TAK1/p38 MAPK pathway. Issue 5 (4th May 2019) - Fan, Yangwei; Li, Mengya; Ma, Ke; Hu, Yuan; Jing, Jiayu; Shi, Yu; Li, Enxiao; Dong, Danfeng
ABSTRACT: Triple-negative breast cancer (TNBC) has a poor prognosis mainly due to insensitivity or resistance to standard anthracycline- and taxane-based chemotherapy, urgently calling for new adjuvants to reverse drug resistance. Dual-target murine double minute 2 (MDM2) and murine double minute X (MDMX) inhibitor has been proved to play a critical part against cancer, particularly focusing on the tremendous potential to enhance the efficacy of doxorubicin (DOX), however little was reported in TNBC. In the present study, we investigated the synergistic antitumor effect of the MDM2/MDMX inhibitor with DOX using three TNBC cell lines, two in situ transplantation tumor models and 214 clinical samples. We observed that the MDM2/MDMX inhibitor combined with DOX could not only inhibit cell vitality and migration and invasion abilities, but also highly inhibit tumor growth in TNBC nude mice. Besides, co-treatment of MDM2/MDMX inhibitor and DOX suppressed epithelial to mesenchymal transition (EMT) through increasing the TAK1-binding protein 1 (TAB1), transforming growth factor β-activated kinase 1 (TAK1) and p38 mitogen-activated protein kinase (MAPK) expression. Small interfering RNA-mediated TAB1 knockdown induced the EMT, desensitized cells to DOX and enhanced the migration and invasion abilities. High MDM2/MDMX expression was positively associated with weak TAB1 expression in 214 TNBC tumor tissues confirmed by immumohistochemical staining and MDM2/MDMX/TAB1 expression was significantly related to TNBC patient survival. These findings indicate that dual-target MDM2/MDMX inhibitor could increase the sensitization of doxorubicin and inhibit migration and invasion abilities in TNBC cells through p38 MAPK pathway activation caused EMT suppression and hence could be useful in TNBC treatments in future.